2003
DOI: 10.1021/ja028557x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ionic Liquid Physical Properties on Lipase Activity and Stability

Abstract: Lipase activity and stability was investigated in dialkylimidazolium and pyrrolidinium-based ionic liquids with a variety of anions including hexafluorophosphate, acetate, nitrate, methanesulfonate, trifluoroacetate, and trifluoromethylsulfonate. The initial rate of lipase-catalyzed transesterification of methyl methacrylate in these ionic liquids and several organic solvents was examined as well as the polytransesterification of divinyl adipate and 1,4-butanediol. Free lipase (Candida rugosa) catalyzed the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
344
0
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(374 citation statements)
references
References 32 publications
14
344
0
16
Order By: Relevance
“…For instance, ILs containing alkyl groups between 10 and 14 carbon atoms are considered toxic toward bacteria and fungi. Designing ILs with alkyl groups shorter than 10 carbon atoms may avoid microbial toxicity (Pernak et al 2003 (Kaar et al 2003) . The conclusion from all of these studies is that simple alterations in the chemistry of ILs can greatly reduce toxicity of IL to microorganisms and enzymes used in the downstream conversion steps.…”
Section: Approaches To Manage Il Toxicitymentioning
confidence: 99%
“…For instance, ILs containing alkyl groups between 10 and 14 carbon atoms are considered toxic toward bacteria and fungi. Designing ILs with alkyl groups shorter than 10 carbon atoms may avoid microbial toxicity (Pernak et al 2003 (Kaar et al 2003) . The conclusion from all of these studies is that simple alterations in the chemistry of ILs can greatly reduce toxicity of IL to microorganisms and enzymes used in the downstream conversion steps.…”
Section: Approaches To Manage Il Toxicitymentioning
confidence: 99%
“…It has been suggested that ionic liquids containing the anions Cl -, Br -, NO 3 -, and CF 3 SO 3 -denature enzymes owing to their higher basicity and, hence, higher affinity for hydrogen bonds. 22,40 There are diverse opinions concerning the effect of fluorinated anions, such as BF 4 and PF 6 , on the enzyme's lifetime. Some reports suggest that since charge can be distributed over several fluorine atoms, the hydrogen bond affinity is minimized between the solvent and the enzyme and that, consequently, there is no interference with the internal hydrogen bonding network of the enzyme, maintaining its secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…(12) tetraflouroborate, (13) hexaflourophosphate, (14) hexafluoro antimonate, (15) nitrate, (16) tosylate, (17) triflate, (18) bromide, (19) chloride, (20) iodide, (21) triflouroacetate (22) perchlorate (23) germanium chloride, (24) bis(trifluoromethylsulfonyl) imide, (25) aluminium chloride, (26) aluminium tetrachloride, (27) acetate, (28) benzoate reactions can often be recovered from RTILs by means of extraction. Supercritical CO 2 , water or organic solvents can be used to recover products and enable the recycling of RTIL for subsequent reactions.…”
Section: Fig (3)mentioning
confidence: 99%